ENTERPRISES RESTRUCTURING AS AN IDEOLOGY OF BUSINESS DEVELOPMENT - Y.K. VERCHENKO (Advanced Engineering Research)
The changes of organization have a different directions depending to company activities.This text is about restructuring as a basic stage of business processes development. To create the flexible, ready-and-able for changes organization we should understand the transformations necessity, then develop the restructuring scheme, after that revitalize organization to create it as open system and renew working up with the spirit of organization (see figure).